A new species of Pseudoechthistatus Pic, 1917 (Coleoptera, Cerambycidae, Lamiinae) from Yunnan, China - Wang, Ping; Xie, Guanglin; Wang, Wenkai (Zootaxa, 2019)
Pseudoechthistatus hei Xie & W. Wang sp. nov. from Yunnan, China is described and illustrated.